HUBUNGAN JENIS ALAT KONTRASEPSI HORMONAL DENGAN TINGKAT KELAINAN TIROID PADA PASANGAN USIA SUBUR (PUS) DI KLINIK LITBANG GAKI MAGELANG TAHUN 2013-2014 - Mulyani, Dwi (Jurnal Kesehatan Masyarakat (Undip), 2016)
Iodine deficiency disorders is a nutritional problem in Indonesia today. The impact of these issues affect is the survival and quality of human resources. Indicator to determine abnormalities of thyroid function due to iodine deficiency either by examination of TSH (Thyroid Stimulating Hormone) and fT4. Hormonal contraceptives is one cause of thyroid function abnormalities. The aim of this study was to determine the relationship type of hormonal contraceptive with levels of thyroid abnormalities in fertile age couple. Observational cross-sectional study conducted in a population of couples of fertile age couple who visit the Clinical Research of IDD Magelang in 2013 - 2014. Methods of sampling is by random sampling. Chi square test was used to determine the relationship type of hormonal contraceptive with levels of thyroid disorders on 115 people were divided into 3 groups, namely the contraceptive pill as many as 11 people, 90 people injectable contraceptives and contraceptive implants as many as 14 people. The results showed at 9.1% incidence rate of hyperthyroidism in sample with the contraceptive pill, 26.6% in injectable contraceptives is 26.6%, and implant is 50%. Chi-square test showed no significant relationship between the type of hormonal contraceptive with the level of thyroid abnormalities (p = 0.23). Need to do counselling about GAKI (definition, causes, consequences, and prevention), especially for pregnant women.